(untitled) (Research, Society and Development, 2020)
The theme healthy eating has become an exponent within school education, however little addressed in science education and, in particular, in early Childhood Education. In this sense, the objective of this work was to analyze how the visit to the fair, as a non-institutionalized non-formal education space, can contribute to the promotion of a healthy diet for children in early Childhood Education. The research has a qualitative approach, pedagogical intervention. Three techniques of information constitution were used: visit to the fair; science wheels and feeding time. For analysis, Discursive Textual Analysis (DTA) was used. Observou-se três categorias:changes in attitudes regarding food choices; school community participation and exploration of sensory qualities of fruits and vegetables. It is considered that the visit to the fair enabled students to change their behavior in relation to their food, from the family-school-market trader, contributing to contextualized science education and closer to its reality.